Strategic Implementation of Public Relations Management in Strengthening School Branding and Enhancing Public Trust in Islamic Primary Education - Muhammad Taufiq; Diningrum Citraningsih (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of public relations management in enhancing school branding within an Islamic primary education institution. The research focuses on the execution of public relations functions, communication strategies, supporting and inhibiting factors, and their contribution to shaping the school’s image. This study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observations, and documentation involving the school principal as the main informant. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that public relations management has not been systematically organized and still tends to function administratively rather than strategically. Although the school has implemented various communication strategies with parents and the community through meetings and social media, school branding is primarily strengthened by flagship programs and institutional achievements. The study implies that strengthening organizational structure, communication planning, and human resources in public relations management is essential to develop sustainable and competitive school branding.